Spatiotemporal characteristics of the setting and its influence on the performance of the attack during freeball complex in volleyball - Lamprogeorgou Μαρία; Drikos Σωτήριος; Sotiropoulos Κωνσταντίνος; Barzouka Καρολίνα (Inquiries in Physical Education and Sport, 2025)
The purpose of this study was to analyse the performance of the setting, in relation to the spatiotemporal characteristics of setting in freeball complex (KV) in both genders. First and third contact performance was also recorded, to identify any relationships between the three. Nine hundred and eight passes (N = 908) from 48 volleyball matches (24 from each gender) of the World Championships of 2022 were examined and analyzed. The researcher’s intra and inter-observer reliability was checked using Cohen’s Kappa index and showed values of 0.92 and 0.89, respectively. Descriptive statistics and inferential analysis with the χ2 test were used to analyse the variables and examine their relationship. The level of statistical significance was defined as p<0.05, with data analysis conducted using the statistical programs SPSS v.29 and Startgraphics v5.1. The results showed that male setters were of higher quality in their settings than female setters (p<0.001), especially when directing their settings to zones 1 and 4 (p=0.007 and p<0.001), when using the second fast tempo (p=0.003) and when receiving an excellent previous action (p=0.02). In addition, it seemed that the quality of the setting influenced the effectiveness of the attack (p=0.02). The percentage of excellent settings was 38.2% for men and 25.4% for women. Attack effectiveness was 54% for men and 46.3% for women. This study promises to enhance our understanding of an underexplored complex and provide valuable insights to the sport’s coaching and strategy.